Epidemics and the health of African nations - Mazibuko-Makena, Zamanzima (The Mapungubwe Institute for Strategic Reflection (MISTRA), 2019)
News footage of disease in Africa is a familiar sight. Yet these outbreaks are often presented out of context, with no reference to the conditions that have triggered them. MISTRA's new book, Epidemics and the Health of African Nations, aims to redress that. Researchers and practitioners from within the continent explore why Africa is so vulnerable to disease, and show how this vulnerability is closely linked to political and economic factors. They demonstrate how these same factors determine the way epidemics are treated. Authors extract lessons from case studies in different parts of Africa; challenge conventional frameworks about disease to argue for a 'syndemics' approach that takes into account the interrelationship between disease and political and socio-economic contexts; explore challenges of Africa's future. They argue that a well-functioning health system is at the core of a country's capacity to counter an epidemic. This volume brings African experts together to probe possible solutions to the continent's heavy burden of disease. The insights offered will be helpful in devising policy for the control of disease and the combatting of epidemics in Africa.